2011
DOI: 10.1016/s1413-8670(11)70142-8
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle antibodies and cryoglobulinemia are associated with advanced liver fibrosis in Brazilian hepatitis C virus carriers

Abstract: Cryoglobulinemia and non-organ-specific-autoantibody are biomarkers of autoimmunity of the chronic infection caused by hepatitis C virus (HCV). In this work, we report the association between the presence of smooth muscle antibodies (SMA) and cryoglobulinemia and chronic liver disease in HCV carriers. Sixty-five untreated HCV patients, 38 women and 27 men were included in this study. Cryoglobulinemia was tested by cryoprecipitation, SMA by indirect fluorescent antibody test, and liver fibrosis and hepatocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Previous studies, as well as the current study, have shown that in Brazil and worldwide, hepatitis C more commonly affects individuals who are between the fourth and fifth decades of life (38 to 42%) 21,22 ; in addition, the majority of those affected are male (60.5 to 76%) 21,23 , and cirrhosis is present in 4 to 21% of patients 3,24 . In Brazil, HCV genotype 1 is associated with prevalence rates that vary between 50.3 and 88.5%, while genotype 2, which was not detected in this study, has a lower prevalence rate that ranges between 0.7 and 8.8% 25 .…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies, as well as the current study, have shown that in Brazil and worldwide, hepatitis C more commonly affects individuals who are between the fourth and fifth decades of life (38 to 42%) 21,22 ; in addition, the majority of those affected are male (60.5 to 76%) 21,23 , and cirrhosis is present in 4 to 21% of patients 3,24 . In Brazil, HCV genotype 1 is associated with prevalence rates that vary between 50.3 and 88.5%, while genotype 2, which was not detected in this study, has a lower prevalence rate that ranges between 0.7 and 8.8% 25 .…”
Section: Discussionsupporting
confidence: 66%
“…We had previously demonstrated that advanced stage of fibrosis in Brazilian patients is associated with cryoglobulinemia. 21 …”
Section: Discussionmentioning
confidence: 99%